THE IMPACT ON REPAYMENT, ENVIRONMENT AND MOTIVATION TO STAFF PERFORMANCE AT CATTLE FARMER COOPERATIVE IN KUNINGAN - Nani Suryani; Robi Awaluddin; Ayus Ahmad Yusuf (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
The institutional success strongly affected employee’s performance, because of the performance of employees in a good company is very influential on the sustainability of the company in achieving its goal, namely seeking the maximum profit. Therefore, for companies that want to be successful, it is essential to encourage their human resources. This scientific paper aim is to examine and analyze the effect of repayment, environment and motivation on employee performance at Karya Nugraha Jaya Kuningan multipurpose cooperative. The descriptive-quantitative is the methode that adopt in this paper. The research object is located in Jl. Raya Cipari Cigugur, Kuningan Regency, West Java, during January to August 2021. The population in this study were all employees of the Karya Nugraha Jaya multipurpose cooperative Kuningan which consist of 77 staff. The data used in this study is primary data, that is data collected by researchers directly from the first source or object of research conducted. Survey by questionnaire instrument was the data collection technique and run by ordinary last square regression for data analysis. The result showed that repayment, environment and work motivation continuously had a positive and significant impact on staff performance. in particular, repayment, environment and motivation each have a significant positive effect to performance of workers.